2015
DOI: 10.1111/tid.12459
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus 2 hepatitis in a lung transplant recipient: a diagnostic challenge

Abstract: Herpes simplex virus (HSV) hepatitis is a rare and serious complication in immunocompromised patients. We report the case of an HSV hepatitis occurring 4 years after lung transplantation in a cystic fibrosis patient. The presentation was nonspecific, mimicking acute cholecystitis; orogenital signs were absent. The diagnosis was made based on viral cultures performed during cholecystectomy and confirmed by blood quantitative polymerase chain reaction. Although the diagnosis and treatment were delayed, the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…S olid organ transplant recipients are highly susceptible to infections that sometimes have uncommon clinical manifestations (1)(2)(3). Etiologic diagnosis of hepatitis is even more problematic in organ transplant recipients because a wide range of possible drug toxicities induced by immunosuppressive therapies must be considered (4). Diagnosing unexplained hepatitis remains a challenge, as exemplified by 74 cases of acute hepatitis of unknown etiology reported in children in the United Kingdom, 3 cases in Spain, and up to 5 possible cases in Ireland (5).…”
mentioning
confidence: 99%
“…S olid organ transplant recipients are highly susceptible to infections that sometimes have uncommon clinical manifestations (1)(2)(3). Etiologic diagnosis of hepatitis is even more problematic in organ transplant recipients because a wide range of possible drug toxicities induced by immunosuppressive therapies must be considered (4). Diagnosing unexplained hepatitis remains a challenge, as exemplified by 74 cases of acute hepatitis of unknown etiology reported in children in the United Kingdom, 3 cases in Spain, and up to 5 possible cases in Ireland (5).…”
mentioning
confidence: 99%
“…The clinical course may be more severe and insidious in LT recipients; additionally, the response to the antiviral therapy is slower [20]. Although mucocutaneous involvements are usually asymptomatic, diffuse mucocutaneous lesions may occur and, if progressive, may extend to the esophagus or lung [21]. In our study, we detected the mucocutaneous involvement in 92.3% of the patients, disseminated disease were in 6.1% of the patients, Also, it was observed that majority of the patients who developed more than one viremia episode had acute and/or chronic rejection.…”
Section: Resultsmentioning
confidence: 99%
“…In advanced stage, fibroblast proliferation and fibrosis of meningeal collagen are finally fund that can lead to an event of arachnoid and piamater thickening, even to mutual adhesion of them. In the last stage, it can cause a blockage of apertura medialis ventriculi quarti, apertura lateralis ventriculi quarti, ring pool of midbrain that in turn formed hydrocephalus [21]. Polysaccharide antigen examinations of staphylococcus aureus capsular in serum and cerebrospinal fluid are contributed to diagnose the cryptococcosis infection of the nervous system.…”
Section: Discussionmentioning
confidence: 99%